Spin scattering and noncollinear spin structure-induced intrinsic anomalous Hall effect in antiferromagnetic topological insulator MnBi_{2}Te_{4} - Seng Huat Lee; Yanglin Zhu; Yu Wang; Leixin Miao; Timothy Pillsbury; Hemian Yi; Susan Kempinger; Jin Hu; Colin A. Heikes; P. Quarterman; William Ratcliff; Julie A. Borchers; et al. (Physical Review Research, 2019)
MnBi_{2}Te_{4} has recently been established as an intrinsic antiferromagnetic (AFM) topological insulator—an ideal platform to create quantum anomalous Hall insulator and axion insulator states. We performed comprehensive studies on the structure, nontrivial surface state, and magnetotransport properties of this material. Our results reveal an intrinsic anomalous Hall effect arising from a noncollinear spin structure for the magnetic field parallel to the c axis. We observed negative magnetoresistance under arbitrary field orientation below and above the Néel temperature (T_{N}), providing clear evidence for strong spin fluctuation-driven spin scattering in both the AFM and paramagnetic states. Furthermore, we found that the nontrivial surface state opens a large gap (∼85meV) even far above T_{N}. Our findings demonstrate that the bulk band structure of MnBi_{2}Te_{4} is strongly coupled with the magnetic property and that a net Berry curvature in momentum space can be created in the canted AFM state. In addition, our results imply that the gap opening in the surface states is intrinsic, likely caused by the strong spin fluctuations in this material.